Definition of Anthaxia (A.) hackeri species-group with description of a new species from China (Coleoptera: Buprestidae) - Obořil, Martin; Baňař, Petr (Zootaxa, 2019)
A new species Anthaxia (Anthaxia) tichyi sp. nov. from Yunnan, Southern China, is described, illustrated, including male genitalia and compared with the most similar species Anthaxia (A.) cupressi Bílý, 2005. The new species belongs to newly defined Anthaxia (Anthaxia) hackeri J. Frivaldszky, 1884 species-group.